2014
DOI: 10.1186/1471-2393-14-217
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section – an appraisal of some predictive factors in Lagos Nigeria

Abstract: BackgroundSeveral maternity units in the developing world lack facilities for caesarean section and often have to transfer patients in extremis. This case controlled study aimed to appraise predictive factors for caesarean section.MethodsOne hundred and fifty two consecutive women with singleton pregnancies who had caesarean section were studied. The next parturient with normal delivery served as control. Variables such as age, parity, marital status, booking status, past obstetric history, weight, height, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 21 publications
11
36
0
Order By: Relevance
“…[12][13][14][15][16] Similar patterns were reported from the studies done in Sokoto, Gwagwalada, Zaria, Gombe, Maiduguri, Birnin Kebbi, Birnin Kudu, Sagamu, Lagos, Awka and Jos. [17][18][19][20][21][22][23][24][25][26]28 It was found that, among the leading indications for elective caesarean section in this study were previous caesarean section, breech presentation, suspected fetal macrosomia, abnormal lie and presentation, and twin and higher order multiple pregnancies which are a common trend. Some (5.6%) of the elective caesarean sections were done for prevention of mother to child transmission of HIV; this is relatively high, close to the 7.34% reported in Calabar and reflective of the prevalence of HIV in the south-south region of the country.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[12][13][14][15][16] Similar patterns were reported from the studies done in Sokoto, Gwagwalada, Zaria, Gombe, Maiduguri, Birnin Kebbi, Birnin Kudu, Sagamu, Lagos, Awka and Jos. [17][18][19][20][21][22][23][24][25][26]28 It was found that, among the leading indications for elective caesarean section in this study were previous caesarean section, breech presentation, suspected fetal macrosomia, abnormal lie and presentation, and twin and higher order multiple pregnancies which are a common trend. Some (5.6%) of the elective caesarean sections were done for prevention of mother to child transmission of HIV; this is relatively high, close to the 7.34% reported in Calabar and reflective of the prevalence of HIV in the south-south region of the country.…”
Section: Discussionmentioning
confidence: 97%
“…In teaching hospitals, documented caesarean section rate was 30.3% in Port Harcourt, 25.6% in Calabar, 27.6% in Enugu, 18.5% in Nnewi, 16.4% in Abakaliki, 11.3% in Sokoto, 21.4% in Abuja, 24.5% in Zaria, 19.8% in Gombe, 11.8% in Maiduguri, 17.69% in Birnin Kudu, 20.3% in Birnin Kebbi, 32.9% in Sagamu, and 40.1% in Lagos. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] In general hospitals, 10.4% was documented in Awka and 5.39% in Calabar, while a private hospital in Jos recorded 8.9%. [26][27][28] This trend exists despite a population level rate as low as 2%, suggesting that assess to caesarean section is skewed; whereas a lot of women lack access to caesarean section to save their lives and that of their babies, some might be undergoing unnecessary procedures.…”
Section: Introductionmentioning
confidence: 99%
“…16 On another hand, ptresent rate is much lower than the rate of 40.1% found in study in Lagos-Nigeria and 43% rate from public hospitals in Brazil. 17,18 Present high caesarean section rate is due to high rate of emergency sections (85.0%), where referral cases are managed from 5 districts and their peripheries as it is the only tertiary care facility in South Kivu Health Division.…”
Section: Discussionmentioning
confidence: 99%
“…However, this metric may not be an accurate predictor of the facility’s ability to perform a CS. Many healthcare facilities within Nigeria cannot offer a CS, and ambulance services are virtually non-existent [25]. In fact, one study demonstrated that only 1 in 21 health facilities in Nigeria is equipped to perform CS [26].…”
Section: Introductionmentioning
confidence: 99%